Compliance with mandatory reporting of clinical trial results on ClinicalTrials.gov: cross sectional study - Prayle, A.P.; Hurley, M.N.; Smyth, Alan R. (British Medical Association, 2012)
Objective To examine compliance with mandatory reporting of summary clinical trial results (within one year of completion of trial) on ClinicalTrials.gov for studies that fall under the recent Food and Drug Administration Amendments Act (FDAAA) legislation.